Use of glucosamine and chondroitin supplements in relation to risk of colorectal cancer: Results from the Nurses' Health Study and Health Professionals follow‐up study. Issue 9 (18th July 2016) - Kantor, Elizabeth D.; Zhang, Xuehong; Wu, Kana; Signorello, Lisa B.; Chan, Andrew T.; Fuchs, Charles S.; Giovannucci, Edward L.
Abstract : Recent epidemiologic evidence has emerged to suggest that use of glucosamine and chondroitin supplements may be associated with reduced risk of colorectal cancer (CRC). We therefore evaluated the association between use of these non‐vitamin, non‐mineral supplements and risk of CRC in two prospective cohorts, the Nurses' Health Study and Health Professionals Follow‐up Study. Regular use of glucosamine and chondroitin was first assessed in 2002 and participants were followed until 2010, over which time 672 CRC cases occurred. Cox proportional hazards regression was used to estimate relative risks (RRs) within each cohort, and results were pooled using a random effects meta‐analysis. Associations were comparable across cohorts, with a RR of 0.79 (95% CI: 0.63–1.00) observed for any use of glucosamine and a RR of 0.77 (95% CI: 0.59–1.01) observed for any use of chondroitin. Use of glucosamine in the absence of chondroitin was not associated with risk of CRC, whereas use of glucosamine + chondroitin was significantly associated with risk (RR: 0.77; 95% CI: 0.58–0.999). The association between use of glucosamine + chondroitin and risk of CRC did not change markedly when accounting for change in exposure status over follow‐up (RR: 0.75; 95% CI: 0.58–0.96), nor did the association significantly vary by sex, aspirin use, body mass index, or physical activity. The association was comparable for cancers of the colon and rectum. Results support a protective association between use of glucosamine and chondroitin and risk of CRC. Further study is needed to better understand the chemopreventive potential of these supplements. Abstract : What's New? In this prospective study, the authors asked whether regular use of glucosamine and chondroitin supplements might reduce the risk of colorectal cancer (CRC). They found that the combination was associated with a statistically significant, 23% reduced risk of colorectal cancer (CRC). These results align with prior observations from the VITamins And Lifestyle (VITAL) study, and may reflect an anti‐inflammatory effect of these supplements. Given the need for safe, effective, and easily implemented CRC preventive strategies, these results merit further study.